PENGUATAN PENDAMPINGAN BACA TULIS AL-QUR’AN SISWA-SISWI KELAS 1-3 SDN TAPAAN 2 KOTA PASURUAN - Nuril Laila; Wiwin Ainis Rohtih (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2025)
This service aims to strengthen assistance in reading and writing the Koran for students in grades 1-3 at SDN Tapaan 2, Pasuruan City. In the context of religious education, the ability to read and write the Koran is a basic skill that must be instilled from an early age. The method used in this service is interactive learning activities that involve students directly. sThe results of this service show a significant increase in the students' ability to read and write the Al-Qur'an.